Loneliness, worries, anxiety, and precautionary behaviours in response to the COVID-19 pandemic: A longitudinal analysis of 200,000 Western and Northern Europeans - Tibor V. Varga; Feifei Bu; Agnete S. Dissing; Leonie K. Elsenburg; Joel J. Herranz Bustamante; Joane Matta; Sander K.R. van Zon; Sandra Brouwer; Ute Bültmann; Daisy Fancourt; Klaus Hoeyer; Marcel Goldberg; et al. (Elsevier, 2021)
Background: In response to the COVID-19 pandemic, governments around the world instituted various public-health measures. Our project aimed to highlight the most significant similarities and differences in key mental-health indicators between four Western and Northern European countries, and identify the population subgroups with the poorest mental-health outcomes during the first months of the pandemic. Methods: We analysed time-series survey data of 205,084 individuals from seven studies from Denmark, France, the Netherlands, and the UK to assess the impact of the pandemic and associated lockdowns. All analyses focused on the initial lockdown phase (March-July 2020). The main outcomes were loneliness, anxiety, and COVID-19-related worries and precautionary behaviours. Findings: COVID-19-related worries were consistently high in each country but decreased during the gradual reopening phases. While only 7% of the respondents reported high levels of loneliness in the Netherlands, percentages were higher in the rest of the three countries (13-18%). In all four countries, younger individuals and individuals with a history of mental illness expressed the highest levels of loneliness. Interpretation: The pandemic and associated country lockdowns had a major impact on the mental health of populations, and certain subgroups should be closely followed to prevent negative long-term consequences. Younger individuals and individuals with a history of mental illness would benefit from tailored public-health interventions to prevent or counteract the negative effects of the pandemic. Individuals across Western and Northern Europe have thus far responded in psychologically similar ways despite differences in government approaches to the pandemic. Funding: See the Funding section.